MORPHOLOGICAL VARIATION AND STATUS OF THE PLANTAIN SQUIRREL Callosciurus notatus (Boddaert, 1785) IN INDONESIA - Ibnu Maryanto; Maharadatunkamsi Maharadatunkamsi; A. Suyanto (Treubia, 2002)
The study of morphological variation of the plantain squirrel Callosciurusnotatus was done based on MZB (Museum Zoologicum Bogoriense) collections. A total of 160 adult specimens from Sumatra, Bangka, Serutu, Siantan-Anamba, Kalimantan, Jawa, Madura, Bali and Selayar Islands. Indonesia were examined. Thirty four skulls, dental and dentary characters were measured. Univariate and multivariate statisticalanalyses were applied to asses morphological variation.The results show that the population of plantain squirrel from Sumatra,Kalimantan and Jawa overlaps in discriminant function space indicating low variation in skull, dentary and dental size. The Maduran was suggested as an intermediate form between Kalimantan and Jawa; Bangka, Belitung, Batam cluster together with Sumatra; Natuna with Jawa; Serutu with Kalimantan; and Siantan appears to be betweenSumatra, Kalimantan and Jawa. There are two subspecies in Sumatera (C. n. vittatus and C. n. tapanulius) and one in Jawa (e. notatus notatus) and Kalimantan (C. n. dulitensis). The colour differences detected between populations within an island of Sumatra is not sufficient to justify that they subspecifically distinct within an island, except for the Tapanuli populations.